Case Report: Focal, generalized, or both: does generalized network involvement preclude successful epilepsy surgery? - Cui, Cathy K.; Wong, Wui-Kwan; Wong, Chong H.; Gill, Deepak; Fong, Michael W. K. (Frontiers in Network Physiology, 2024)
Two cases presenting with focal seizures where scalp EEG had prominent features of a Developmental and Epileptic Encephalopathy (DEE). Case 1: A 17-year-old male with complex motor seizures and EEG demonstrated slow spike-and-wave and generalized paroxysmal fast activity (GPFA). Case 2: A 12-year-old male with startle-induced asymmetric tonic seizures whose EEG also had slow spike-and-wave. Both patients were assessed with intracranial EEG and focal cortical resections resulted in long-term seizure freedom and resolution of generalized findings. These cases exemplify patients with focal epilepsy with networks that share similarities to generalized epilepsies, and importantly these features did not preclude curative epilepsy surgery.